2002
DOI: 10.7326/0003-4819-137-3-200208060-00006
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ϵ4 Allele, Elevated Midlife Total Cholesterol Level, and High Midlife Systolic Blood Pressure Are Independent Risk Factors for Late-Life Alzheimer Disease

Abstract: The association between the apoE epsilon4 allele and Alzheimer disease does not seem to be mediated by vascular factors. The apoE epsilon4 allele, elevated midlife total cholesterol level, and high midlife systolic blood pressure are independent risk factors for Alzheimer disease. The risk for Alzheimer disease from treatable factors--elevated total cholesterol level and blood pressure--appears to be greater than that from the apoE epsilon4 allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
358
1
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(393 citation statements)
references
References 28 publications
12
358
1
14
Order By: Relevance
“…Additionally, 10 authors were contacted for missing or ambiguous information, of whom 7 responded. Two additional studies were found from cross-references [16,17], of which one could be included [16]. This resulted in 8 cross-sectional studies, 5 casecontrol studies, 10 prospective cohort studies and 1 study with both cross-sectional and prospective analyses (designated as cross-sectional regarding study quality).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 10 authors were contacted for missing or ambiguous information, of whom 7 responded. Two additional studies were found from cross-references [16,17], of which one could be included [16]. This resulted in 8 cross-sectional studies, 5 casecontrol studies, 10 prospective cohort studies and 1 study with both cross-sectional and prospective analyses (designated as cross-sectional regarding study quality).…”
Section: Resultsmentioning
confidence: 99%
“…Of those focusing on MI, four studies did not find an association with dementia, Alzheimer's disease, vascular dementia or decline to mild cognitive impairment or dementia [20][21][22][23]. Three studies did find a significant association between MI and dementia [18], Alzheimer's disease and Alzheimer's disease/ vascular dementia (but only for MI ascertained at the late-life visit) [16], and possible dementia/mild cognitive impairment [19]. Two out of the four AP studies did find that AP increased the risk of dementia or possible dementia/mild cognitive impairment [19,24], whereas the other two studies did not find an association [22,23].…”
Section: Prospective Cohort Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Although a number of epidemiological studies have shown that hypercholesterolemia is related to an increased risk of developing AD or mild cognitive impairment (48)(49)(50), other results, which do not fit in with this conclusion, have also been reported. In 2005, for example, Reitz et al (51) observed no effects of cholesterol and triglyceride levels on the cognitive ability of aged individuals, while other studies demonstrated that high levels of total cholesterol or low-density lipoprotein (LDL)-cholesterol correlated with a decreased AD (52) and dementia risk (53).…”
Section: Epidemiological Studiesmentioning
confidence: 87%
“…Hypercholesterolemia in midlife is a risk factor for developing AD decades later (Kivipelto et al, 2002). Statins not only lower serum cholesterol levels, but also improve vasoreactivity in peripheral arteries and large cerebral arteries and are associated with a reduced prevalence of AD (Masse et al, 2005).…”
Section: Introductionmentioning
confidence: 99%